التوزيع الجغرافي لكاربونات الكالسيوم فى ترب محافظة أربيل - أ.م.د. ليلى محمد قهرمان (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
(10) different sections were selected within the Governorate of Erbil to dig profiles and study their soils, the selection of sections based on variation in the nature of prevailing climatic conditions, especially rainfall rates and the kind of the basic rocks and parent materials from which the soil was formed as well as irrigation methods used and how to use the soil for agriculture. After describing the locations of the profiles and description of the soil, samples of each layer were taken for laboratory analyzing to estimate same physical and chemical properties, including CaCO3 %, the results showed significant differences in CaCO3 % between different sites horizontally from south to north side of the study area as well as vertically from the surface layer towards the sub-surface and deep layers based on the kind of the basic rocks and parent materials from which the soil was formed. By using the pearson correlation coefficient at a 1% probability level, the relationships showed the negative high significant relation between the values of rain lines and CaCO3% and a significant negative relation between Silt % and CaCO3 % in the surface layers, while the association with the Sand % was high significant negative relation in the deep layers,positive high significant relation between CaCO3% and each of pH and EC in the surface and the deep layers consequently and negative significant relation with O.M% in the surface layers.